A Generic Method for Multi Word Extraction from Wikipedia - Bekavac, Božo; Tadić, Marko (2008)
This paper presents the generic method for multiword expression extraction from Wikipedia. The method is using the propreties of this specific encyclopedic genre in its HTML format and it relies on the intention of the autors of articles to link to other articles. The relevant links were processed by applying local regular grammars within the NooJ development envi-ronment. We tested the method on a Croatian version of Wikipedia and we present the results obtained.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG